Authority and the Mountaineer in Cormac McCarthy's Appalachia - Rikard, Gabe (McFarland & Co., Inc., Publishers, 2013)
"The author uses Michel Foucault's theories on power, resistance and discipline to analyze the interactions of mountaineers and the authorities who have attempted to "modernize" them. The book shows how Cormac McCarthy manipulates Appalachian regional images while simultaneously engaging in a form of archeology of Appalachian constructs"--